9-N-n-alkyl Berberine Derivatives: Hypoglycemic Activity Evaluation - Mikhail V. Khvostov; Elizaveta D. Gladkova; Sergey A. Borisov; Marina S. Fedotova; Nataliya A. Zhukova; Mariya K. Marenina; Yulia V. Meshkova; Nicolae Valutsa; Olga A. Luzina; Tatiana G. Tolstikova; Nariman F. Salakhutdinov (MDPI AG, 2022)
Several novel 9-N-n-alkyl derivatives of berberine (C5, C7, C10, C12) were synthesized. They were analyzed in vitro and in vivo for their hypoglycemic activity. In vitro studies showed that the derivatives with shorter alkyl substitutes at concentrations ranging from 2.5 to 10 μM were able to stimulate glucose consumption by HepG2 cells more prominently than the derivatives with longer substitutes (C10 and C12). All compounds demonstrated a better effect compared to berberine. Their impact on cells' viability also depended on the alkyl substitutes length, but in this case, C10 and C12 derivatives demonstrated the best results. A similar correlation was also found in the OGTT, where the C5 derivative demonstrated a pronounced hypoglycemic effect at a dose of 15 mg/kg and C12 was less effective. This compound was further investigated in C57BL/6Ay mice for four weeks and was administered at a dose of 15 mg/kg. Pronounced effect of C12 on carbohydrate metabolism in mice was discovered: there was a decrease in fasting glucose levels and an increase in glucose tolerance in OGTT on the 14th and 28th days of the experiment. However, at the end of the experiment, signs of hepatosis exacerbation and an increase in the content of hepatic aminotransferases in blood were found.